2017
DOI: 10.3389/fendo.2017.00039
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Chemokines in Fracture Repair

Abstract: Chemokines are a family of small cytokines that share a typical key structure that is stabilized by disulfide bonds between the cysteine residues at the NH2-terminal of the protein, and they are secreted by a great variety of cells in several different conditions. Their function is directly dependent on their interactions with their receptors. Chemokines are involved in cell maturation and differentiation, infection, autoimmunity, cancer, and, in general, in any situation where immune components are involved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 99 publications
2
51
0
Order By: Relevance
“…The role of CCL3 in myeloma‐induced bone disease was investigated by Vallet et al They found osteocalcin expression downregulated and osteoblast mineralization inhibited by CCL3 (Vallet et al, ). This observation is confirmed by other authors, who report CCL3 to impair mineralization in fracture healing and high serum levels of CCL3 to be associated with delayed fracture healing (Edderkaoui, ; Fu et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…The role of CCL3 in myeloma‐induced bone disease was investigated by Vallet et al They found osteocalcin expression downregulated and osteoblast mineralization inhibited by CCL3 (Vallet et al, ). This observation is confirmed by other authors, who report CCL3 to impair mineralization in fracture healing and high serum levels of CCL3 to be associated with delayed fracture healing (Edderkaoui, ; Fu et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…RNA microarrays of the fracture site among the group that received NSAID during the active time revealed an upregulation of genes signalling cytokines associated with the polarization of macrophage cells from M1 phenotype to M2 such as Retnla, FIZZ1 and IL-4R1 during bone healing 47 . This group also showed expression of genes www.nature.com/scientificreports www.nature.com/scientificreports/ associated with the recruitment of mesenchymal stem cells and the initiation of the angiogenesis process such as CXCR4 and CCL12 44 (Table S4). In addition, the group that received NSAID during the active phase demonstrated a downregulation of transcripts associated with the expression of pro-inflammatory cytokines including Stat1, IL-9, IL-6ra, and IL-18 48,49 .…”
Section: Discussionmentioning
confidence: 94%
“…Our gene ontology analysis of the differentially expressed genes suggested that the timing of NSAID administration after bone fracture affected several signalling pathways such as: the inflammation mediated pathway, the interleukin, T-cell and B-cell activation signalling pathways, and the EGFR signaling pathway. Studies have demonstrated the effect of these pathways [44][45][46] on regulating cytokine signaling and the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Under inflammatory conditions, EGF is a potent inducer of angiogenesis and bone growth by significantly upregulating secretion of vascular endothelial growth factor (VEGF) and bone morphogenetic protein-2 (BMP-2), an osteoinductive growth factor (50). MCP-1 has also been shown to be a key cytokine involved in both inflammation and bone remodeling, in particular with processes that include neutrophil migration, macrophage infiltration, and angiogenesis (51). Similarly, LIX and RANTES are known for their chemotactic and pro-inflammatory properties that have both been associated with the necessary inflammatory phase during the fracture repair process (52,53).…”
Section: Prevention Of Tcr and T Cell Activation Inhibits One Of The mentioning
confidence: 99%